Guiding Systems Engineering Research for Enhanced Impact in the Development of Increasingly Complex Cyber‐Physical Systems. Issue 4 (9th February 2023) - McDermott, Tom; Verma, Dinesh
ABSTRACT: In 2019, the research council of the Systems Engineering Research Center (SERC), a US Defense Department sponsored university affiliated research center (UARC), developed a set of roadmaps (SERC 2019) structuring and guiding four areas of systems engineering research: digital engineering, velocity, security, and artificial intelligence (AI) and autonomy. This paper presents the development of these roadmaps and the key underlying transformation aspects.